Die funksie van die belydenis en die dogma in die struktuur van die Nederduitsch Hervormde Kerk en die implikasies daarvan vir die predikant - Pont, A. D. (Hervormde teologiese studies, 1985)
The function of the Confession and Doctrine in the structure of the NHK and the implications thereof for a minister of the WordThe whole question of the function of the Confession and Doctrine in the structure of the NHK is mainly a question of church order. This matter is treated, in the first place, by looking at history and the calvinist roots of the Church. Because the Confessio Belgica names the true preaching of the Word as one of the marks of the Church, it is of paramount importance for the Church to maintain true preaching. The norm by which true preaching is measured, is the regula fidei, i e the Bible and in the second place the Confession and the Doctrine. In the form of subscription by the ministers of the Word they acknowledge that Confession is in accordance with the Word and therefore a true norm for measuring true preaching. Three cases of alleged heresy committed by ministers are examined to determine in which way the Church Councils applied the mentioned norms.